Disgust sensitivity is associated with heightened risk perception. Issue 5 (4th May 2019) - Karg, Simon Tobias; Wiener-Blotner, Aaron; Schnall, Simone
Abstract: Disgust is a versatile emotion that is not only elicited by threats to one's physical health but that has also recently been linked to social and especially moral concerns. Building on the hypothesis that disgust can be seen as part of a broader loss aversion system, four studies demonstrate that disgust sensitivity is linked to heightened risk perception. A preliminary study and Study 1 established a moderate correlation of disgust sensitivity with risk perception. Studies 2 and 3 confirmed the effect while controlling for potential affective influences, including current mood, or trait anxiety, respectively. Importantly, we find that the correlation is also independent of gender and age, and that disgust sensitivity is associated with a broad range of risk domains, including recreational, social, ethical, financial, and health and safety risks. Therefore, disgust may be part of a general risk aversion mechanism aimed at guiding behavior in uncertain situations.